Protocol for the systematic review of return-to-activity criteria in adolescent patients following an anterior cruciate ligament reconstruction - Romanchuk, Nicholas J.; Livock, Holly; Lukas, Kenneth J.; Del Bel, Michael J.; Benoit, Daniel L.; Carsen, Sasha (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Anterior cruciate ligament (ACL) rupture is a debilitating knee injury associated with sequela such as joint instability and progressive degeneration. Unfortunately, following surgical ACL reconstruction in adolescents, the rates of ACL graft failure range from 17 to 19%. A contributing factor to the high reinjury rate in this population may be the limited evidence regarding appropriate criteria for allowing unrestricted return-to-activities (RTA) postoperatively. Several systematic reviews have already sought to develop a consensus on what criteria should be utilized for releasing patients to unrestricted sports activities; however, these reviews have focused on adult populations, a group at much lower risk for reinjury. Our objective is to systematically examine the literature and identify the criteria used when determining unrestricted RTA following an ACL reconstruction in an adolescent population. Methods Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic search will be performed of the MEDLINE/PubMed, Cochrane, Embase, CINAHL, and SPORTDiscus electronic databases. Searches will be conducted from January 1, 2000, until submission of the final review. Studies will be identified that include adolescent patients (10–18 years old) undergoing a primary ACL reconstruction and which have specified the criteria used to determine RTA. Each article will be independently screened by two reviewers. To supplement the electronic database search, citations within all included studies will be manually reviewed. Reviewers will record the RTA assessment utilized and the rates of ACL reinjury through a standardized data extraction sheet. Reviewers will resolve full-text screening and data extraction disagreements through discussion. Synthesis of the collected data will focus on compiling and mapping the most commonly used types of RTA criteria. Discussion This systematic review will determine the most commonly used RTA criteria in adolescent patients post-ACL reconstruction. This will help future interventions build more effective adolescent-specific RTA assessments through the validation of current RTA criteria as well as the implementation of new criteria according to the identified literature gaps.